COMMUNICATIVE ACTS IN THE TEXTS OF THE NEW TESTAMENT GOSPELS: MENTAL AND AXIOLOGICAL, MORAL AND ETHICAL FACTORS - MELNYK, YAROSLAV (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The key issue of the article is the typology of communicative acts in the texts of the New Testament; the communicative acts are discussed from mental and axiological, moral and ethical perspectives. The goal of the article is to establish, discuss and interpret the main parameters of communication between Christ, His followers and opponents. The accent is made on the components of Christian world view as a discourse factor in the New Testament’s texts. The analysis results are extrapolated to the sphere of discourse creation, its linguistic, philosophical, ethical and communicative aspects. The principles of human existence and the existence of information space in the early 21st century are discussed.